Mechanical and Durability Properties of High-Performance Concrete Incorporating Fibers and Algerian Natural Pozzolans in Chloride Attack - Chalah, Lyes; Talah, Aissa; Ghernouti, Youcef (International Journal of Engineering and Technology Innovation, 2022)
This study aims to assess the effect of sodium chloride attack on the mechanical and durability properties of high-performance concrete (HPC) based on fibers and natural pozzolans. The resistance of specimens against chemical attack is determined by the unit weight, compressive strength, splitting-tensile strength, chloride ion permeability, apparent gas permeability, and visual inspection after 28, 90, 180, and 365 days of testing. A total of three types of concrete are assessed: reference concrete (RC), HPC, and high-performance fiber-reinforced concrete (HPFRC) stored in tap water and aggressive water (i.e., a 10% NaCl solution). The test results demonstrate that the presence of fibers negatively affects the permeability of HPC. However, HPC and HPFRC remain stable and are not influenced by the NaCl solution compared to RC. The natural pozzolans attenuate the side effect of fibers by occupying voids (i.e., the filler effect) and generating denser products (i.e., the pozzolanic reaction) in the cement matrix.